Reframing “Organizations and Society” from the Escrevivências: for a Form of Management from and in the Gaps - Rocha da Silva, Fernanda; de Padua Carrieri, Alexandre (Organizações & Sociedade, 2022)
This is not a conventional manuscript that follows the established norms of research in organizational studies, but it does not give up the scientificity required by academia. It is yet another way of doing and writing, as it occurs with the practices developed by those who have been secluded from the prevailing way of organizing in Brazil. Therefore, we propose to rethink the forms of management from the experiences of lacunar subjects and knowledge forms, from the social-historical perspective on the formation of the boundaries of this scientific field. To do so, we adjust our lenses to frame what lies outside the privileged enunciative locus of the instrumental rationality ruling the field and come across Carolina Maria de Jesus and her escrevivências about a reality that has been unnoticed by management practices according to the success model of this form of rationality. Therefore, we present a theoretical and scientific article, in which literature is employed as source material to outline the proposed reflections and reframe “organizations and society” from the know-how of those who have been underprivileged by dominant reason.